Optimasi Peningkatan Laba Produksi Abon dengan Menggunakan Algoritma Genetika (Studi Kasus UKM Poklahsar Berkah Lumintu - Tulungagung) - Khoirin Nisa Fitrianur; Rekyan Regasari Mardi Putri; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Poklahsar Berkah Lumintu is a Small and Medium Business (SME) located in Gondosuli Village, Gondang District, Tulungagung Regency. As a minapolitan area with the main results of Catfish and Patin Fish. SMEs are producing various kinds of processed fish-based meals by utilizing every part of the fish. The best selling products sold on this SME namely catfish abon, Tuna abon , Patin fish abon, and Salmon abon. It Have been Proved that the abon sales is increased from year to year. In 2011 sales of catfish abon were 6336 packs, and experienced a significant increase in 2015 of 41,000 packs. Determination of the amount of abon production is done only according to the owner's estimate that is subjective only, so often there is excess stock abon.Untuk able to overcome these problems, it needs an analysis based on sales data so as to minimize the remaining stock abon.At the right amount of production can increase the profit industry . Optimization is needed to maximize profits with certain time, materials, and capital in accordance with the limitations that have been set. Optimization of increased production abon in this study using genetic algorithm. After the implementation and research, the best result is 50 with population size = 100, generation size = 90, cr = 0.8, and mr = 0.2